Abundance and Diversity of Aerobic Anoxygenic Phototrophic Bacteria in Polar Plant Microbiomes - Mäkinen, Emilia A.; Franz, Ole; Ihalainen, Janne A.; Helander, Marjo; Nissinen, Riitta; Mathew, Suni A.; Saloniemi, Irma; Saikkonen, Kari (Physiologia Plantarum, 2025)
ABSTRACT Here, we examined the occurrence of plant-associated aerobic anoxygenic phototrophic bacteria (AAPB) across polar regions. Recently found in polar soils and cold-climate plants, AAPBs are photoheterotrophs that rely on environmental organic carbon but capture solar energy via anoxygenic photosynthesis. We revealed the abundance of AAPBs by extracting bacteria from plant tissues and imaging the colonies with bacteriochlorophyll-based near-infrared fluorescence. The taxonomic distribution of AAPBs was determined via 16S rRNA gene analysis. From the northern hemisphere, we describe AAPBs from the leaf endo- and phyllospheres of numerous sub- and Arctic plant species in Northern Finland, Svalbard, and Greenland. In the southern hemisphere, we focused on AAPBs in the root and leaf endospheres and the phyllospheres of Deschampsia antarctica in Chilean Patagonia and maritime Antarctica. Additionally, we describe AAPB from the tissues of several other plant species in Patagonia. We found AAPBs commonly associated with the sampled plant species across both hemispheres. A diversity of Alphaproteobacteria was found to contain the AAP capability: at all sampling sites, Sphingomonas was the most abundant taxon (up to 60%), while Methylobacteria made up a notable proportion of sub-Arctic and sub-Antarctic AAPB samples (up to 32%). In contrast to previous studies describing Methylobacteria frequently in various plant communities, AAP-containing Methylobacteria were virtually absent from our high-latitude sites. With diverse AAPB taxa found ubiquitously across polar regions and plant tissues, our results call attention to the potential ecological interaction between AAPBs and their plant hosts.
Publisher: John Wiley & Sons, Ltd
Keywords: Antarktis; biodiversitet; biogeografi; biologi; mikroorganismer; polarområdene

Global Marine Flyways Identified for Long-Distance Migrating Seabirds From Tracking Data - Morten, Joanne M.; Carneiro, Ana P. B.; Beal, Martin; Bonnet-Lebrun, Anne-Sophie; Dias, Maria P.; Rouyer, Marie-Morgane; Harrison, Autumn-Lynn; González-Solís, Jacob; Jones, Victoria R.; Garcia Alonso, Virginia A.; Antolos, Michelle; Arata, Javier A.; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad-scale oceanic migration routes (?marine flyways?) used by multiple pelagic, long-distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989?2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long-distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad-scale flyways followed by most pelagic migratory seabirds tracked to-date at an ocean-basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure-of-eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind-driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean-basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.
Publisher: John Wiley & Sons, Ltd Article number: e70004
Keywords: Sørishavet; biogeografi; biologging; sjøfugler; økologi

Advances and shortfalls in knowledge of Antarctic terrestrial and freshwater biodiversity - Pertierra, L. R.; Convey, P.; Barbosa, A.; Biersma, E. M.; Cowan, D.; Diniz-Filho, J. A. F.; de los Ríos, A.; Escribano-Álvarez, P.; Fraser, C. I.; Fontaneto, D.; Greve, M.; Griffiths, H. J.; et al. (Science, 2025)
Antarctica harbors many distinctive features of life, yet much about the diversity and functioning of Antarctica?s life remains unknown. Evolutionary histories and functional ecology are well understood only for vertebrates, whereas research on invertebrates is largely limited to species descriptions and some studies on environmental tolerances. Knowledge on Antarctic vegetation cover showcases the challenges of characterizing population trends for most groups. Recent community-level microbial studies have provided insights into the functioning of life at its limits. Overall, biotic interactions remain largely unknown across all groups, restricted to basic information on trophic level placement. Insufficient knowledge of many groups limits the understanding of ecological processes on the continent. Remedies for the current situation rely on identifying the caveats of each ecological discipline and finding targeted solutions. Such precise delimitation of knowledge gaps will enable a more aware, representative, and strategic systematic conservation planning of Antarctica.
Publisher: American Association for the Advancement of Science
Keywords: Antarktis; biodiversitet; biogeografi; biologi; biomonitorering; mikroorganismer; økologi; økosystemer

Surface darkening by abundant and diverse algae on an Antarctic ice cap - Thomson, Alex Innes; Gray, Andrew; Colesie, Claudia; Thomas, Naomi; Moulton, Hannah; Convey, Peter; Smith, Alison G.; Fretwell, Peter; Peck, Lloyd; Davey, Matthew P. (Nature Communications, 2025)
Algal blooms play important roles in physical and biological processes on glacial surfaces. Despite this, their occurrence and impacts within an Antarctic context remain understudied. Here, we present evidence of the large-scale presence, diversity and bioalbedo effects of algal blooms on Antarctic ice cap systems based on fieldwork conducted on Robert Island (South Shetland Islands, Antarctica). Algal blooms are observed covering up to 2.7 km2 (~20%) of the measured area of the Robert Island ice cap, with cell densities of up to 1.4 × 106 cells ml−1. Spectral characterisation reveal that these blooms increase melting of the ice cap surface, contributing up to 2.4% of total melt under the observed conditions. Blooms are composed of typical cryoflora taxa, dominated by co-occurring Chlorophyceae, Trebouxiophyceae, and Ancylonema. However, morphological variation and genetic diversity in Ancylonema highlight the influence of regional endemism and point to a large and under-characterised diversity in Antarctic cryoflora.
Article Number: 2647
Keywords: Antarktis; Sør-Shetlandsøyene; biogeografi; biologi; kryosfæren; snøalger; økologi

Global biogeography of marine amphipod crustaceans: latitude, regionalization, and beta diversity - Arfianti, Tri; Costello, Mark J (Marine Ecology Progress Series, 2020)
Studying the biogeography of amphipod crustaceans is of interest because they play an important role at lower trophic levels in ecosystems. Because they lack a planktonic larval stage, it has been hypothesized that marine benthic amphipod crustaceans may have short dispersal distances, high endemicity, and spatial turnover in species composition, and consequently high global species richness. In this study, we examined over 400000 distribution records of 4876 amphipod species, and identified 12 regions of endemicity. The number and percent of endemic species peaked at 30°-35°S and coincided with 3 of these regions of high endemicity: Australia, New Zealand, and southern Africa. Pelagic species of marine amphipod crustaceans were more cosmopolitan than benthic species. The latitudinal patterns of richness (alpha, gamma, and ES50) and species turnover were at least bimodal. Most occurrence records and greater alpha and gamma richness were in mid-latitudes, reflecting sampling bias. Both ES50 and beta diversity had similar richness in the tropics, mid-latitudes, and on the Antarctic shelf around 70°S. These 2 indices exhibited a sharp dip in the deep Southern Ocean at 55°S. ES50 peaked at 30°-35°S and a small dip was apparent near the equator at 5°-10°N. Beta diversity was driven mostly by turnover rather than nestedness. These findings support the need for conservation in each realm of species endemicity and for amphipods, particularly in Antarctica and the coastal mid-latitudes (30°-35°S) of the Southern Hemisphere. KEYWORDS: Endemicity · Latitudinal gradients · Conservation · Species richness · Species turnover
Keywords: Sørishavet; biogeografi; crustacea; krepsdyr; marin biologi; marine økosystemer; zoogeografi